The role of tax potential in stimulating the effectiveness of innovation in the digital economy - Maksimchuk Olga; Maznitsa Elena; Chizho Larisa (E3S Web of Conferences, 2021)
The conditions of the digital economy dictate new challenges in order to correct structural imbalances; answers to these challenges are possible in the format of innovations. Since the beginning of the pandemic, it has become even more obvious that enterprises that have actively introduced innovations, in particular digital technologies and products, have become successful players in all markets. And tax stimulation has always been the most effective tool for innovation in economic activity.The purpose of this study is to substantiate the role of tax potential in stimulating the effectiveness of innovation in the digital economy. The object of research is the tax potential of the territory. The subject of the research is tax stimulation for the efficiency of innovation in the digital economy. The article presents the advantages and disadvantages of the existing tax system for stimulating innovation in Russia, the tax benefits as the main tool for stimulating innovation in the Russian Federation, the proposals for improving legislation on taxes and fees.